Evaluasi Pengalaman Pengguna pada Website International Office Universitas Primakara Menggunakan User Experience Questionnaire (UEQ) - Permana, Dewa Made Aditya; Paramitha, A. A. Istri Ita; Dewi, Eka Grana Aristya (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2024)
The study aimed to evaluate the user experience of the Primakara University International Office website. Primakara University developed the International Office website as part of its efforts to improve its competitiveness and educational quality at the international level. Through the International Office, the university can offer programs such as student exchange, international internships, and international scholarships to provide valuable experiences for students. User experience evaluation was conducted using the User Experience Questionnaire (UEQ) method with 30 respondents. The results were positive, with the final score for the average score for all aspects being greater than 0.8. The aspects of attractiveness received scores of 2.21, perspicuity received scores of 2.03, efficiency 2.12, dependability 1.86, stimulation 1.67, and novelty 1.25. The results of the test were classified as between "Good" and "Excellent."